2013
DOI: 10.1177/1087057113502085
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Characterization of a Kinetic In Vitro Human Co-Culture Angiogenesis Model Using Clinically Relevant Compounds

Abstract: Angiogenesis, the formation of new vessels from preexisting vessels, involves multiple cell types acting in concert to cause endothelial cell proliferation, migration, and differentiation into microvascular arrays. Under pathologic conditions, microenvironment changes result in altered blood vessel production. Historically, in vitro angiogenesis assays study individual aspects of the process and tend to be variable, difficult to quantify, and limited in clinical relevance. Here, we describe a kinetic, quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Indeed, Ang-Tie signaling pathways are known to play a role in both promoting angiogenesis and quiescence [72][73][74]. The expression of Tie2 protein on EC plasma membrane aligns with previous studies of ECs in vitro [31,32,75,76] and in vivo [77]. Furthermore, Ang-Tie signaling pathways have been identified as one of the escaping mechanisms tumor vasculature develops in response to anti-VEGF treatment, which made Ang-Tie a novel drug target for antiangiogenesis therapy [78,79].…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, Ang-Tie signaling pathways are known to play a role in both promoting angiogenesis and quiescence [72][73][74]. The expression of Tie2 protein on EC plasma membrane aligns with previous studies of ECs in vitro [31,32,75,76] and in vivo [77]. Furthermore, Ang-Tie signaling pathways have been identified as one of the escaping mechanisms tumor vasculature develops in response to anti-VEGF treatment, which made Ang-Tie a novel drug target for antiangiogenesis therapy [78,79].…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the good permeability properties, these compounds exhibited adequate potency preventing migration of HUVEC cells in vitro, an assay that is used to evaluate antiangiogenic behavior. 23 Notably, compound 13 showed the best balance of MAP4K4 inhibition, permeability, microsomal stability, and cellular potency.…”
mentioning
confidence: 99%
“…In the current study, we used the CellPlayer 96-well kinetic angiogenesis PrimeKit assay produced by ESSEN Bioscience, and based on the HUVEC/NHDF co-culture model 27) . Wolfe et al 28) demonstrated that the HUVEC/NHDF co-culture model is suitable to screen the effect of drugs and natural products on angiogenesis at the early stages. Currently, most liquid forms of commercial soft polymer materials include phthalate esters as plasticizers [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…The various in vivo methods used include the Mile's assay, chicken embryo chorioallantoic membrane method, and the Matrigel subcutaneous implantation method; however, these methods have various limitations 26) . Therefore, in recent year numerous in vitro methods have been developed to assess angiogenesis [26][27][28] . In the current study, we used the CellPlayer 96-well kinetic angiogenesis PrimeKit assay produced by ESSEN Bioscience, and based on the HUVEC/NHDF co-culture model 27) .…”
Section: Discussionmentioning
confidence: 99%